(3cJGH aj GdMSHIs - (3eMeO Hf eMeO GdSbWis
(3ChdgG (B:s
(3hCeG hdGjI GdMSjI bGd Gddg JYGdi hdJcf efce CeI jOYhf Edi GdNjQ hjCeQhf HGdeYQha hjfghf Yf GdefcQ s
(3BNQgG (B:s
(3jJTHghf HGdeSdejf hef NhGUg Cfg jcJH dQO GdSGQb hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HBNQg fbhd eNJdaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdSjGSI hGdGLJeGYs